Smart Agriculture Remote Monitoring System Using Low Power IOT Network (International Journal of Food and Nutritional Sciences, 2022)
Climate changes and rainfall has been erratic over the past decade. Due to this in recent era, climate-smart methods called as smart agriculture is adopted by many Indian farmers. One of the important applications of IoT is Smart Agriculture. It reduces wastage of water, fertilizers and increases the crop yield. Smart agriculture is an automated and directed information technology implemented with the IoT (Internet of Things). IoT is developing rapidly and widely applied in all wireless environments. In this project, sensor technology and wireless networks integration of IoT technology has been studied and reviewed based on the actual situation of agricultural system. Temperature sensor, Moisture sensor and pH sensor which senses the temperature, moisture content and pH in the soil which are connected to Raspberry pi. A combined approach with internet and wireless communications, Remote Monitoring System (RMS) is proposed. Nowadays IoT is the growing technology in the present era. As considering all the aspects into picturization we proposed a new methodology in which a farmer can easily identify the status of his field and proceed for the crop to be irrigated. In this we calculate the Temperature, Humidity, SoilMoisture, and pH of the field. By visualizing all the parameters, we considered the respective individual can easily identify the nature of his field and the crop that can be cultivated in the field.